IS PATIENT SAFETY AT THE HEART OF MEDICAL EDUCATION IN INDONESIA? REFLECTION ON THE IMPACT OF THE NATIONAL EXAMINATION - Rachmadya Nur Hidayah (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2019)
ABSTRACT Background: National examinations in Indonesia (UKMPPD) has been implemented since 2007 as a quality assurance method for medical graduates and medical schools. The impact of UKMPPD has been studied since then, where one of the consequences were related to how it affected medical education and curricula. This study explored the consequences of UKMPPD, focusing on how the students, teachers, and medical schools’ leaders relate the examination with patient care. This study aimed to explore the impact of UKMPPD on medical education, which focusing on the issue of patient safety. Methods: This study was part of a doctoral project, using a qualitative method with a modified grounded theory approach. The perspectives of multiple stakeholders on the impact of the UKMPPD were explored using interview and focus groups. Interviews were conducted with medical schools’ representatives (vice deans/ programme directors), while focus groups were conducted with teachers and students. A sampling framework was used by considering the characteristics of Indonesian medical schools based on region, accreditation status, and ownership (public/ private). Data was analysed using open coding and thematic framework as part of the iterative process. Results: The UKMPPD affected how the stakeholders viewed this high-stakes examination and the education delivered in their medical schools. One of the consequences revealed how stakeholders viewed the UKMPPD and its impact on patient care. Participants viewed the UKMPPD as a method of preparation for graduates’ real clinical practice. The lack of reference for patient safety as the impact of the UKMPPD in this study showed that there were missing links in how stakeholders perceived the examination as part of quality assurance in health care. Conclusion: The UKMPPD as a high-stakes examination has a powerful impact in changing educational policy and programmes in Indonesia. However, in Indonesia, the examination brought in the reflection on how the “patient” element was lacking from medical education. This research offers an insight on the concept of patient safety in Indonesia and how the stakeholders could approach the issue. Keywords: UKMPPD, national licensing examination, impact, competence, patient safety, curriculum